Vectors in the works of Varlam Shalamov- poet and prosaic - Meskin, V.A.; Agarwal, Shraddha (Opción, 1970)
The article reveals the theme of Varlam Shalamov's creative search in poetry and prose, his movement from realism with a bit of romanticism to the literary fact. In this context, in particular, the author explains the radical changes in his views on the purpose of the art of speech, on human nature, reveals the presence of significant difference in the pathos in the sequence of his lyrical and epic works. From the analysis of many specific works, it follows that Shalamov was critical, selective about classical traditions that his poetics of his work changed significantly depending on the tasks set by the master. The article is based on the findings of many researchers-predecessors.